2018
DOI: 10.1017/s0960258518000302
|View full text |Cite
|
Sign up to set email alerts
|

Potential impact of global warming on seed bank, dormancy and germination of three succulent species from the Chihuahuan Desert

Abstract: We assessed inter-seasonal dynamics of seed banks, dormancy and seed germination in three endemic Chihuahuan Desert succulent species, under simulated soil warming conditions. Hexagonal open top-chambers (OTCs) were used to increase soil temperature. Seeds of Echinocactus platyacanthus (Cactaceae), Yucca filifera and Agave striata (Asparagaceae) were collected and buried within and outside OTCs. During the course of one year, at the end of each season, seed batches were exhumed to test viability and germinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 44 publications
0
19
0
4
Order By: Relevance
“…Even some works where the cactus seeds were stored under controlled conditions have demonstrated that these can germinate after various years (Flores et al 2005, Sánchez-Salas et al 2006 up to a maximum of 10 years (Alcorn & Martin 1974, Fearn 1977, Trujillo et al 2014. Few studies have directed their efforts toward evaluating the viability of cactus seeds under natural conditions and their permanence in seed banks (Álvarez-Espino et al 2014, Aragón-Gastélum et al 2018.…”
Section: Seed Dormancy Rojas-aréchiga and Vázquez-yanesmentioning
confidence: 99%
See 2 more Smart Citations
“…Even some works where the cactus seeds were stored under controlled conditions have demonstrated that these can germinate after various years (Flores et al 2005, Sánchez-Salas et al 2006 up to a maximum of 10 years (Alcorn & Martin 1974, Fearn 1977, Trujillo et al 2014. Few studies have directed their efforts toward evaluating the viability of cactus seeds under natural conditions and their permanence in seed banks (Álvarez-Espino et al 2014, Aragón-Gastélum et al 2018.…”
Section: Seed Dormancy Rojas-aréchiga and Vázquez-yanesmentioning
confidence: 99%
“…There are few studies that have submitted the seeds to environmental conditions and have examined their viability after different burial periods (Bowers 2000, 2005, Matías-Palafox 2007Olvera-Carrillo et al 2009, Cheib & Souza 2012, Goodman et al 2012, Álvarez-Espino et al 2014, Ordoñez-Salanueva et al 2017, Lindow-López et al 2018a, Aragón-Gastélum et al 2018 or have assessed the effective seed bank, extracting the seeds from the soil in different times of the year (Montiel & Montaña 2003). Only the studies of Bowers (2005) and Ordoñez-Salanueva et al (2017) shows two species (Mammillaria grahamii and Polaskia chende) capable of possessing a long-term, continuous seed bank (up to at least five years) according to the classification of Bakker et al (1996).…”
Section: Seed Dormancy Rojas-aréchiga and Vázquez-yanesmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, studies should examine the fitness consequences of temporal shifts in germination [15,16]. By exploring the effects of climate change on the processes by which seeds germinate, future studies will generate realistic predictions of recruitment from seed under climate change [29,30], and inform conservation strategies [26].…”
Section: Germinationmentioning
confidence: 99%
“…Some studies have determined the response of seed dormancy release to single environmental factors such as temperature [5,7,[16][17][18], winter duration [11,19] and seed/soil moisture content [13][14][15] during cold stratification. The results of these studies suggested that global warming could impact the dynamics of seed dormancy release and thus delay or enhance plant regeneration from seeds [20][21][22][23]. However, climate change is not only a change in temperature, but it also may alter the duration of winter and soil moisture content [20].…”
Section: Introductionmentioning
confidence: 99%